Pengaruh Pemberian Pupuk Kandang Ayam dan Pupuk Hayati Bio-Extrim Terhadap Pertumbuhan dan Produksi Tanaman Kangkung Darat (Ipomoea reptans Poir.) - Gulo, Primuadin; Zulfida, Ida; Jabat, Yelfi Yana Linda (JURNAL AGROPLASMA, 2024)
This research was conducted to determine the effect of chicken manure and the bio-fertilizer Bio-Extrim on the growth and production of water spinach plants. (Ipomoea reptans Poir). This research was conducted at the experimental field of the Faculty of Agriculture at the University of Community Development Indonesia (UPMI) in Medan. Wakaf Street, Market 12, Marendal 2, Patumbak District, Deli Serdang Regency, at an elevation of 40 meters above sea level. (mdpl). This research will begin in June 2024 and continue until July 2024. This research uses a Factorial Randomized Block Design (FRBD) method consisting of 2 factors: 1) The application of chicken manure (A) which consists of 4 levels, namely: A0 = 0 tons/ha (Control), A1 = 20 tons/ha equivalent to 2 kg/plot, A2 = 40 tons/ha equivalent to 4 kg/plot, A3 = 80 tons/ha equivalent to 8 kg/plot. 2) The application of the biofertilizer Bio-Extrim (B), consisting of 4 levels, namely: B0 = 0 l/ha (Control), B1 = 4 l/ha equivalent to 0.4 l/plot, B2 = 8 l/ha equivalent to 0.8 l/plot, B3 = 16 l/ha equivalent to 1.6 l/plot. A total of 16 combinations were obtained, repeated 3 times, resulting in 48 experimental units that were randomly arranged. Based on the results of the experiment, it can be concluded that the combination of the bio-fertilizer Bio-Extrim and chicken manure has no significant effect on the root length of water spinach plants. The concentration of chicken manure does not significantly affect the root length of water spinach, and the concentration of the bio-fertilizer Bio-Extrim also does not significantly affect the root length of water spinach. Keywords: chicken manure, bio-fertilizer bio-extrim, water spinach plants